2014
DOI: 10.1107/s2052520614010063
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure study of binary thorium compounds from first principles theory and comparisons with experiment

Abstract: High-pressure study of binary thorium compounds from first principles theory and comparisons with experiment Kanchana, V.; Vaitheeswaran, G.; Svane, A.; Heathman, S.; Gerward, Leif; Olsen, J. Staun

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…He found that the transformation from B1 to B2 structure at high pressures about 200 GPa. Many researches on LaN [4][5][6][7][8] and ThN [9][10][11] were also reported to provide useful insight on the high-pressure properties by using first principle (FP) calculations. The structural phase transformation from B1 to B2 also is found in LaN [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…He found that the transformation from B1 to B2 structure at high pressures about 200 GPa. Many researches on LaN [4][5][6][7][8] and ThN [9][10][11] were also reported to provide useful insight on the high-pressure properties by using first principle (FP) calculations. The structural phase transformation from B1 to B2 also is found in LaN [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These properties make them suitable for applications in nuclear reactors. Binary compounds of thorium has been studied at large scale due to their peculiar chemical and physical properties [21][22][23][24]. Yong Xu et al, reported that the thermoelectric performance of materials can be enhanced by tuning the size parameter in topological insulators [25].…”
Section: Introductionmentioning
confidence: 99%